Narrating China's Governance Stories in Xi Jinping's Speeches - People's Daily, Department of Commentary; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2020)
This open access book captures and elaborates on the skill of storytelling as one of the distinct leadership features of Xi Jinping, the General Secretary of the Communist Party of China and the President of the People$1 (Bs Republic of China. It gathers the stories included in Xi$1 (Bs speeches on various occasions, where they conveyed the essence of China$1 (Bs history and culture, its reform and development, and the principles of China$1 (Bs participating in global governance and cooperating with other countries to build a community of common destiny. The respective stories not only convey abstract and profound concepts of governance in comparatively straightforward language, but also create an immediate emotional connection between the narrator and the listener. In addition to the original stories, extensive additional materials are provided to convey the original context in which each was told, including when and to whom Xi told it, helping readers attain a deeper, intuitive understanding of their relevance.s
Preface -- Introduction: .-Part 1 About the Interior -- On Incorrupt Government: "When the officials become corruptible and unfair, the regime is going into decline" -- On Characters and Morals: "To enter politics, a person should cultivate his moral character and enrich himself with virtues first" -- On Self-improvement: "If you want to enhance your ability, you must study; if you want to make the blade sharp, you must sharpen it"- On Governance: "Empty talk endangers the nation, practical work brings prosperity" -- Part 2 About Diplomacy -- On People-to-people Friendship: "The key to sound relations between states lies in amity between the people" -- On Intercourse Between Nations: "Of the things brought about by the rites, harmony is the most valuable" -- On Cultural Exchange: "It is the very nature of things to be unequal in quality" -- On Historical Affinity: "Distance cannot separate true friends who feel so close even when they are thousands of miles apart" -- On Xi Jinping's Personal Experience: Never forget why you started.
Keywords: China -- History; Ethnology -- Asia; Culture; Political science; History of China; Asian Culture; Governance and Government